Investigating effective factors in the model of high organizational commitment in government organizations in charge of educational and cultural affairs - Seyed Alireza Mirjafari; Abdul Khaliq Gholami Anarestan; Karam Elah Daneshfard (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to investigate the effective factors in the model of high organizational commitment in government organizations in charge of educational and cultural affairs. The current research is practical in terms of its purpose, and survey-exploratory in terms of the research implementation method; and it is specifically based on structural equation modeling. The statistical population of the research includes managers and experts of government organizations in charge of educational and cultural affairs. 217 people were selected as a sample using the method of determining the sample size of Cochran's formula. The collection tool in this research is a researcher-made questionnaire. confirmatory factor analysis was performed in order to confirm the final research model. SPSS software was used to analyze data from; and AMOS software was used to design the final research model. The findings of the research showed that the components of selection and recruitment, training, compensation, job conditions, and work conscience were effective in the final constructivism evaluation model and it shows the appropriate fit of the proposed model. Extended abstract Introduction In today's competitive business environment, which is accompanied by a lot of change and turbulence, the problem of many organizations is not only having more experienced and smarter employees, but finding talented employees with motivation and a positive attitude and committed to work is a fundamental issue for the human resources department of any organization. Organizational commitment is one of the basic elements in achieving organizational goals, and having committed employees in any business will lead to significant results in achieving these goals (Riyanto et al, 2021). Therefore, it is very important to study what helps employees to achieve strong organizational commitment and create motivation, and to learn about the factors that involve and sustain organizational commitment in them (Mohseni & Mousavi, 2022). Organizational commitment is an important occupational and organizational attitude that, during the past years, has been of interest to many researchers in the fields of organizational behavior and psychology, especially social psychology. Organizational commitment is defined as accepting the organization's values and being involved in the organization, and its measurement criteria include the motivation and desire to continue working and accepting the organization's values. Commitment is a kind of support and emotional attachment to the goals and values of an organization, for the sake of the organization itself and away from its instrumental values (a means to achieve other goals) (Hassanian et al, 2022). Therefore, the researcher tries to answer the question: what are the factors in the model of high organizational commitment in government organizations in charge of educational and cultural affairs? Theoretical Framework Organizational commitment is a kind of employee's feeling of attachment and loyalty to organizational work, and when his goal is in accordance with the goals of the organization, he is called committed to the organization (Tabli, Moradi Shahrabak, Irannejad Parizi, 2019). Employees who consider themselves incomplete for a job leave the organization and do not spend much time in the organization, and if they feel ethical behavior from the organization, they have less decision to leave the organization (Wong & Laschinger, 2015; Devi & Vijayakumar, 2015). Organizations can increase the organizational commitment of their employees in two ways. First, organizations can increase employees' understanding of organizational membership, and secondly, organizations can show employees that they are considered by managers, and this is important both theoretically and practically (Bakhtazmaybonab, Roshani, 2019). Organizational commitment can lead to an increase in productivity and a reduction in turnover and absenteeism of employees in the organization (Khan & Jan, 2015). Van et al, (2022) investigated performance management and teacher performance: the role of emotional organizational commitment and burnout. The results showed that the perceived strength of a performance management process is negatively related to teacher burnout, while it is positively related to their performance. Furthermore, the relationship between perceived performance management process strength and teacher performance appears to be indirect, operating mainly through affective organizational commitment. Peyman Niya (2022) investigated the effectiveness of the matrix model on job burnout and organizational commitment of the managers of Ahvaz electricity department. The results showed that the matrix model was effective in reducing job burnout and improving the organizational commitment of managers, so it is suggested to use this approach in organizations to reduce the job burnout of employees. Methodology: In terms of purpose, this research is practical, and in terms of research implementation method; survey-exploratory. The statistical population of the research includes managers and experts of government organizations in charge of educational and cultural affairs, which was considered as 396 people from the city of Tehran, and using the method of determining the sample size of Cochran's formula, 217 people were selected as a sample based on the formula Sampling calculated from the limited population, among which, as a sample, was distributed a researcher-made questionnaire prepared from the qualitative part of the research. This research was conducted in two research stages, the first stage is related to exploratory factor analysis and the second stage is questionnaire confirmation. Discussion and Results: SPSS and AMOS software were used for analysis. According to the results obtained in the selection and recruitment component, it shows that all factor loadings are higher than 0.3. According to the output of Imus, the calculated value of df/2x is 2.07; the presence of df/2x smaller than 5 indicates the appropriate fit of the model. According to the results obtained in the education component, all factor loadings are higher than 0.3. According to the output of Imus, the value of df/2x calculated is 1.80; the presence of df/2x smaller than 5 indicates the appropriate fit of the model. According to the results obtained in the service compensation component, all factor loadings are higher than 0.3. According to the output of Imus, the value of df/2x calculated is 1.54; the presence of df/2x smaller than 5 indicates the appropriate fit of the model. According to the results obtained in the job conditions variable, confirmatory factor analysis method was used. The numbers on the paths are factor loadings, all higher than 0.3. The findings related to the fit indices of job conditions indicate that the CFI, GFI, NFI, RMR and RMSEA indices have an acceptable level, and these good fit characteristics show that the data of this research fit the factor structure of this scale. According to the results in the work conscience variable, all factor loadings are higher than 0.3. The findings related to the outcome fit indices indicate that the CFI, GFI, NFI, RMR and RMSEA indices have an acceptable level and these good fit characteristics show that the data of this research has a good fit with the factor structure of this scale. Conclusion: The current research was conducted with the aim of investigating the effective factors in the model of high organizational commitment in government organizations in charge of educational and cultural affairs. The results of this research are consistent with the results of van et al, (2022), Hoseini Goke (2022), Klimchak (2020), Asgari et al, (2018), Salimzadeh (2017), and Ghaid Amini Harouni et al, (2017). In the selection of research, inquiries, tests and interviews with applicants for employment or admission to universities or offices, as a result of these researches and interviews; the moral, religious and political competence of the applicant is examined, and people who do not have legal conditions are eliminated, and the recruitment leads to a contract between an employee and an employer. Training is one of the most important criteria effective on high commitment and improving productivity in government organizations. In fact, training improves and increases the commitment of employees. The administrative and management system plays a fundamental role in developing countries such as Iran due to the limitations caused by the lack of skilled human resources. Scholars and experts who have left the organizations have evaluated the current situation of the service compensation system in the mentioned organizations as lower than average, and in fact, they do not consider the current service compensation system in these organizations included in the minimum service compensation standard. When employees know that the training they received from the organization contributed to their professional success, they will appreciate their organization for having such a process. This kind of feeling of gratitude will increase the level of commitment of employees in the best way. A distinction must be made between work conscience and faith, because someone can be considerd without religious faith, but when a task is assigned to him, he does it well and correctly without needing external and physical control. According to the present research, it is suggested that government organizations in charge of educational and cultural affairs pay more attention to the criteria of the proposed model, especially human resource management, and remind their employees of their importance by providing appropriate training, and consider complying with them by Organizations and their employees necessary, and try to promote them to increase productivity in the organization. It is suggested that managers pay attention to the transformational leadership style and its application in the university in their management. Through applying the transformational leadership style, they can influence the employees and motivate them to adapt to the changes and increase the level of commitment to change in the university.